Clinical significance of azathioprine active metabolite concentrations in inflammatory bowel disease. Issue 8 (9th July 2004) - Wright, S; Sanders, D S; Lobo, A J; Lennard, L
Abstract : Background and aims: There are conflicting reports on the role of azathioprine (AZA) thioguanine nucleotide (TGN) metabolites in optimising therapy for inflammatory bowel disease (IBD). The aim of this study was to investigate TGN intrapatient variation, and the relationship between TGN concentrations and disease activity in IBD patients taking long term constant dose AZA. Methods: TGN and methylmercaptopurine nucleotide (MeMPN) concentrations were measured at intervals over a two year period. Disease activity was assessed at each clinic visit using the Crohn's disease activity index or Walmsley simple index for ulcerative colitis. Results: Serial TGNs were measured in 159 patients (3–14 TGN assays, median 6). Intrapatient variation in TGN concentrations was 1–5-fold (median 1.6); the incidence of non-compliance was 13%. At the end of two years, 131 patients were evaluable at TGN steady state. Of this group, patients who remained in remission had significantly higher mean TGN concentrations than those patients who developed active disease (median TGNs 236 v 175, respectively; median difference 44 pmol (95% confidence interval 1–92); p = 0.04). MeMPN concentrations were not related to AZA efficacy or toxicity. Conclusions: This study has shown that lower TGN concentrations were linked to the development of active disease, and that TGNs may act as useful markers of compliance. However, it is clear that repeat TGN measurements are required for an unambiguous index of active metabolite exposure. In view of the high intrapatient variability in TGN production over time, TGN measurements may not be currently advocated for routine clinical use.